2010
DOI: 10.1111/j.1440-1746.2010.06239.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C deficiency increases the binucleation of hepatocytes in SMP30 knock‐out mice

Abstract: Therefore, it is concluded that vitamin C deficiency induces an increase of CYP2E1 expression and elevated ROS production, which causes oxidative liver injury and the elevation of hepatocyte binucleation in SMP30 KO mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…2009). These characteristics were observed repeatedly in our own several previous studies (Park et al. 2010a,b), which confirms that vitamin C‐deficient SMP30 mice have a less robust phenotype compared with WT mice.…”
Section: Discussionsupporting
confidence: 84%
“…2009). These characteristics were observed repeatedly in our own several previous studies (Park et al. 2010a,b), which confirms that vitamin C‐deficient SMP30 mice have a less robust phenotype compared with WT mice.…”
Section: Discussionsupporting
confidence: 84%
“…In another study, scavenging of ROS during fetal-neonatal transition resulted in a decrease in the number of binucleated cardiomyocytes (Matsuyama and Kawahara, 2011). A correlative in vivo study was performed in mice, where the authors showed that vitamin C deficiency induces elevated ROS production, which causes oxidative liver injury and the increase of BN hepatocytes (Park et al, 2010). These data indicate a correlation between ROS and BN formation although it is still not known whether there is a direct causal effect.…”
Section: Discussionmentioning
confidence: 91%
“…In these cases, the increase in binucleation could be linked to hepatic recovery processes following toxic injury 114 and usually as a result of oxidative stress generation 114,115 . Confirming the results that present a role of oxidative stress in liver binucleation, it has been already published that vitamin C deficiency induced an increase of cytochrome P450 2E1 (CYP2E1) expression and elevated ROS production, which causes oxidative liver injury and the elevation of hepatocyte binucleation in senescence marker protein 30 (SMP30) knock-out mice 116 .…”
Section: Binucleation and Chemical-driven Liver Damagementioning
confidence: 53%